2021
DOI: 10.3390/foods10061345
|View full text |Cite
|
Sign up to set email alerts
|

Reading Food Experiences from the Face: Effects of Familiarity and Branding of Soy Sauce on Facial Expressions and Video-Based RPPG Heart Rate

Abstract: Food experiences are not only driven by the food’s intrinsic properties, such as its taste, texture, and aroma, but also by extrinsic properties such as visual brand information and the consumers’ previous experiences with the foods. Recent developments in automated facial expression analysis and heart rate detection based on skin color changes (remote photoplethysmography or RPPG) allow for the monitoring of food experiences based on video images of the face. RPPG offers the possibility of large-scale non-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The intensity of these emotions ranges from 0 to 1. Although this software is not fully accurate in its emotion recognition performance [ 6 , 18 ], the analyses of these emotions have been effectively employed in various experimental situations in food research [ 5 , 19 , 20 , 21 , 22 , 27 , 32 ]. In our previous study [ 30 ], we used a different facial expression analysis software.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity of these emotions ranges from 0 to 1. Although this software is not fully accurate in its emotion recognition performance [ 6 , 18 ], the analyses of these emotions have been effectively employed in various experimental situations in food research [ 5 , 19 , 20 , 21 , 22 , 27 , 32 ]. In our previous study [ 30 ], we used a different facial expression analysis software.…”
Section: Discussionmentioning
confidence: 99%
“…Implicit evaluation methods are diverse [ 4 ], encompassing heart rate variability [ 5 , 6 , 7 ], skin temperature [ 8 ], skin blood flow [ 9 , 10 ], skin conductance response [ 11 ], facial expressions [ 3 , 6 , 12 , 13 ], and brain activity [ 14 , 15 , 16 , 17 ]. Among these, facial expression analysis stands out as a relatively straightforward and practical approach, utilizing readily available automatic classifiers for facial affect recognition [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, here, it is worth noting how there may also be a link here between the stereotypical facial expressions that are associated with experiencing the different basic tastes (see Steiner, 1974 , 1979 ; Steiner et al, 2001 ; Spence, 2012 ; Weiland et al, 2010 ) and those that are associated with displays of facial emotion (e.g., Liang et al, 2021 ; cf. de Wijk et al, 2021 ; Greimel et al, 2006 ). 20 This connection certainly makes sense in terms of the increasingly-popular theories of embodied cognition (see Wilson, 2002 ).…”
Section: Food and Behaviour: The Bidirectional Relationship Between Mood And Tastementioning
confidence: 99%
“…Consumers' purchasing decisions are not only affected by the intrinsic sensory properties of the products but also by the extrinsic information that is provided at the time of purchasing. De Wijk et al [5] evaluated the effects of familiarity and branding on the sensory experiences of soy sauces using facial expressions and video-based heart rate measurements. They found that liking and arousal toward the products were affected by taste but not by branding and familiarity.…”
mentioning
confidence: 99%